Toward automatic generation of mvc2 web applications - Mbarki, Samir; Erramdani, Mohammed (INFOCOMP Journal of Computer Science, 2008)
Most of server-side development technologies have emerged, since the invention of CGI in 1993. Facing this diversity and incessant improvement of Web technology, we have the feeling that we are in need of developing a tool which is able to produce the code from UML conception model. This paper examines the application of MDA approach in the engineering of web applications. Two meta-models were designed: The first one for managing UML source models, the seco2 web application models. The transformation rules and mapping algorithm were developed to generate an xml file containing all actions, forms, and forward JSP pages from class diagram that can be used to generate the required code of web application.